Surface finishing method for additive manufacturing copper alloy inner runner structure

By adopting ultrasonic vibration + chemical composite polishing method in the inner runner structure of copper alloys in additive manufacturing, the problem of difficulty in reducing surface roughness in the prior art is solved, and better flow resistance and heat exchange characteristics are achieved.

CN119465159APending Publication Date: 2025-02-18CAPITAL AEROSPACE MACHINERY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411627755.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the surface roughness of the complex inner channel members of copper alloys, affecting the flow resistance characteristics and heat exchange characteristics.

Method used

Using ultrasonic vibration + chemical composite polishing method, the chemical polishing solution of acetic acid aqueous solution and hydrogen peroxide aqueous solution in an environment of 30-40℃, combined with ultrasonic vibration of 40-60kHz can be dissolved and immersed in the flow channel surface of the copper alloy. Corrosion polishing.

Benefits of technology

It effectively reduces the surface roughness of the flow channel structure in the copper alloy, improves the flow resistance characteristics, and improves the heat exchange characteristics of the parts. The polishing time is completed within 20-30 minutes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465159A_ABST
    Figure CN119465159A_ABST
Patent Text Reader

Abstract

The invention relates to an additive manufacturing copper alloy inner runner structure surface finishing method, and belongs to the technical field of additive manufacturing. Preparing a chemical polishing solution; chemical polishing liquid is input into an inner flow channel of the copper alloy structure, and ultrasonic vibration is conducted on the copper alloy structure; clean water is poured into the inner flow channel of the copper alloy structure for cleaning; the inner flow channel of the copper alloy structure is blow-dried through compressed air, and cleaning is completed; the method is used for reducing the surface roughness of copper alloy complex inner flow channel components in the fields of aerospace, energy and chemical industry, removing redundant materials adhered to the inner surfaces of the flow channels, reducing the flow resistance of the flow channels and improving the heat exchange characteristics of inner flow channel structures of parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of additive manufacturing and relates to a surface finishing method for an additively manufactured copper alloy inner flow channel structure. Background Art

[0002] Laser selective melting forming technology is an additive manufacturing technology based on powder bed powder laying. This process can be used to complete the overall manufacturing of complex inner cavity structures such as inner flow channels. For copper alloy components with millimeter-level flow channels in liquid rocket engine combustion chambers, due to the high reflectivity and thermal conductivity of copper alloys to lasers, a larger laser energy input is required to ensure the effective forming of copper alloys. Under large energy input, the surface quality of the inner flow channel after overall laser selective melting is poor, and the surface roughness is generally around 20μm. The roughness of the flow channel surface directly affects the flow resistance characteristics of the entire component and cannot meet the use requirements of the model product. In addition, the thrust chamber flow channel is a variable-section spatial curve structure, and the entire flow channel has a large aspect ratio, generally greater than 500; the flow channel is narrow, and the width is generally between 0.8-2mm. Existing surface finishing technologies such as abrasive flow and ternary vibration cannot effectively reduce the surface roughness of such structures. Summary of the invention

[0003] The technical problem solved by the present invention is: to overcome the shortcomings of the prior art and propose a surface finishing method for an additively manufactured copper alloy inner flow channel structure, which is used to reduce the surface roughness of complex inner flow channel components of copper alloys in the fields of aerospace, energy and chemical industry, remove excess materials adhered to the inner surface of the flow channel, reduce the flow resistance of the flow channel, and improve the heat exchange characteristics of the inner flow channel structure of the part.

[0004] The solution of the present invention is:

[0005] A surface finishing method for an additively manufactured copper alloy inner flow channel structure, comprising:

[0006] Prepare chemical polishing solution;

[0007] The chemical polishing liquid is introduced into the inner flow channel of the copper alloy structure, and the copper alloy structure is subjected to ultrasonic vibration;

[0008] Pour clean water into the inner flow channel of the copper alloy structure for cleaning;

[0009] Use compressed air to dry the inner flow channel of the copper alloy structure to complete the cleaning.

[0010] In the above-mentioned method for surface finishing of an inner flow channel structure of a copper alloy manufactured by additive manufacturing, the chemical polishing liquid includes an acetic acid aqueous solution and a hydrogen peroxide aqueous solution; the ratio of the acetic acid aqueous solution to the hydrogen peroxide aqueous solution is 1:1.

[0011] In the above-mentioned method for surface finishing of an inner flow channel structure of a copper alloy by additive manufacturing, the concentration of acetic acid in the acetic acid aqueous solution is 2-6 g / 100 ml; the concentration of the hydrogen peroxide aqueous solution is 10%-20%.

[0012] In the above-mentioned method for surface finishing of an inner flow channel structure of a copper alloy manufactured by additive manufacturing, the ambient temperature during the ultrasonic vibration is 30-40°C.

[0013] In the above-mentioned method for surface finishing of the inner flow channel structure of the copper alloy in additive manufacturing, under a temperature environment of 30-40°C, the hydrogen ions in the acetic acid aqueous solution react chemically with copper in a strong oxidizing environment of hydrogen peroxide to achieve dissolution and corrosion of the protruding positions on the inner surface of the copper alloy structure.

[0014] In the above-mentioned method for surface finishing of an additively manufactured copper alloy inner flow channel structure, ultrasonic vibration is applied to the outer surface of the copper alloy structure, and vibration-chemical composite polishing is performed on the inner surface of the copper alloy structure.

[0015] In the above-mentioned method for surface finishing of an additively manufactured copper alloy inner flow channel structure, the frequency of ultrasonic vibration is 40-60 kHz.

[0016] In the above-mentioned method for surface finishing of an additively manufactured copper alloy inner flow channel structure, ultrasonic vibration causes the chemical polishing liquid to produce a cavitation effect on the surface of the copper alloy structure; the cavitation collapse produces an explosive jet to further improve the finishing efficiency and shorten the entire polishing time; the polishing time is 20-30 minutes.

[0017] In the above-mentioned method for surface finishing of an additively manufactured copper alloy inner flow channel structure, the inner cavity is cleaned 3-5 times with clean water.

[0018] In the above-mentioned method for surface finishing of an inner flow channel structure of a copper alloy manufactured by additive manufacturing, the temperature of the compressed air is above the dew point temperature; and the pressure of the compressed air is 0.5-0.8 MPa.

[0019] The beneficial effects of the present invention compared with the prior art are:

[0020] (1) The finishing process proposed in the present invention can effectively reduce the surface roughness of the internal flow channel structure of the integral additively manufactured copper alloy and improve the flow resistance characteristics;

[0021] (2) The present invention utilizes H+ in the acetyl solution at a temperature of 30-40°C to react chemically with copper in a strong oxidizing environment of hydrogen peroxide to dissolve and corrode the protruding parts on the surface of the parts as a whole;

[0022] (3) The invention applies ultrasonic vibration to make the chemical solution produce cavitation effect on the surface of the part, and the collapse of the cavitation produces explosive jets to further improve the finishing efficiency and shorten the entire polishing time. The polishing time of the entire flow channel structure is generally 20-30 minutes depending on the structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flow chart of the surface finishing of the copper alloy inner flow channel structure manufactured by additive manufacturing.

[0024] Figure 2 This is a diagram showing the surface finishing effect of the copper alloy inner flow channel structure manufactured by additive manufacturing according to the present invention. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the embodiments.

[0026] The present invention provides a surface finishing method for an additively manufactured copper alloy inner flow channel structure. Aiming at the need to reduce the surface roughness and flow resistance of the overall additively manufactured copper alloy narrow flow channel structure, a finishing technology solution of ultrasonic vibration + chemical composite polishing is proposed to reduce the surface roughness and flow resistance of the inner flow channel.

[0027] Surface finishing method for additively manufactured copper alloy inner flow channel structure, such as Figure 1 As shown, the specific steps include:

[0028] Prepare chemical polishing solution.

[0029] The chemical polishing liquid includes an acetic acid aqueous solution and a hydrogen peroxide aqueous solution; the ratio of the acetic acid aqueous solution to the hydrogen peroxide aqueous solution is 1:1. The concentration of acetic acid in the acetic acid aqueous solution is 2-6g / 100ml; the concentration of the hydrogen peroxide aqueous solution is 10%-20%.

[0030] A chemical polishing liquid is introduced into an inner flow channel of the copper alloy structure, and ultrasonic vibration is performed on the copper alloy structure.

[0031] The ambient temperature during ultrasonic vibration is 30-40°C.

[0032] Under the temperature environment of 30-40℃, the hydrogen ions in the acetic acid aqueous solution react chemically with copper in the strong oxidizing environment of hydrogen peroxide, thereby dissolving and corroding the protruding parts of the inner surface of the copper alloy structure.

[0033] Ultrasonic vibration is applied to the outer surface of the copper alloy structure, and vibration-chemical composite polishing is performed on the inner surface of the copper alloy structure. The frequency of ultrasonic vibration is 40-60kHz. Ultrasonic vibration causes the chemical polishing liquid to produce cavitation effect on the surface of the copper alloy structure; the collapse of cavitation produces explosive jets to further improve the finishing efficiency and shorten the entire polishing time; the polishing time is 20-30 minutes.

[0034] Pour clean water into the inner flow channel of the copper alloy structure for cleaning; clean the inner cavity with clean water 3-5 times.

[0035] Use compressed air to dry the inner flow channel of the copper alloy structure to complete the cleaning.

[0036] The temperature of the compressed air is above the dew point temperature; the pressure of the compressed air is 0.5-0.8Mpa.

[0037] Example

[0038] The surface finishing method of the internal flow channel structure of the additively manufactured copper alloy mainly includes three stages: preparing chemical polishing liquid, surface finishing of the flow channel structure, and flow channel cleaning. The copper and copper alloy materials involved include oxygen-free copper, chromium-zirconium copper, and chromium-niobium copper.

[0039] Step 1: Prepare chemical polishing solution

[0040] Chemical polishing liquid is configured according to the chemical characteristics of copper alloy. The main components of the polishing liquid are acetic acid solution and hydrogen peroxide solution. The concentration of acetic acid in the acetic acid solution is 4g / 100ml, and the concentration of hydrogen peroxide solution is 15%. The two solutions are mixed in a ratio of 1:1.

[0041] Step 2: Vibration-chemical composite polishing

[0042] After the prepared chemical polishing liquid is passed into the inner flow channel, 50kHz ultrasonic vibration is added to the surface of the part, and the part is placed in a 35°C temperature environment for vibration-chemical composite polishing. Polishing mainly uses the H+ in the acetyl solution at a temperature of 35°C to react chemically with copper in a strong oxidizing environment of hydrogen peroxide to dissolve and corrode the protruding parts on the surface of the part as a whole. At the same time, the addition of ultrasonic vibration causes the chemical solution to produce a cavitation effect on the surface of the part, and the collapse of the cavitation produces an explosive jet to further improve the finishing efficiency and shorten the entire polishing time. The polishing time of the entire flow channel structure is generally 26 minutes depending on the structure.

[0043] Step 3: Flow channel cleaning

[0044] When pouring clean water into the inner cavity of the component for cleaning, clean the inner cavity 4 times.

[0045] The inner cavity is blown dry with compressed air to complete the cleaning. The temperature of the compressed air is above the dew point temperature and the pressure is 0.7Mpa.

[0046] After finishing, the surface roughness of the inner flow channel of the copper alloy structure decreased from Ra 29.43μm to Ra 11.2μm. Figure 2 shown.

[0047] The present invention provides a composite finishing process technology of ultrasonic vibration + chemistry. It is mainly used for laser selective melting integral additive manufacturing of copper alloy inner flow channel structure, removing semi-molten powder adhering to the surface of the inner flow channel, reducing the surface roughness of the flow channel, and improving the flow resistance characteristics of the inner flow channel. The ultrasonic vibration + chemical composite finishing process proposed in this patent has the technical advantages of not introducing other redundant materials, no residue, and environmentally friendly polishing liquid. It can effectively solve the technical problems that affect the application of laser selective melting additive manufacturing of copper alloy inner flow channels, such as large flow resistance and the risk of redundant materials.

[0048] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.

Claims

1. A surface finishing method for an additively manufactured copper alloy inner flow channel structure, characterized in that: include: Prepare chemical polishing solution; The chemical polishing liquid is introduced into the inner flow channel of the copper alloy structure, and the copper alloy structure is subjected to ultrasonic vibration; Pour clean water into the inner flow channel of the copper alloy structure for cleaning; Use compressed air to dry the inner flow channel of the copper alloy structure to complete the cleaning.

2. The surface finishing method of the copper alloy inner flow channel structure manufactured by additive manufacturing according to claim 1 is characterized in that: The chemical polishing solution comprises an acetic acid aqueous solution and a hydrogen peroxide aqueous solution; the ratio of the acetic acid aqueous solution to the hydrogen peroxide aqueous solution is 1:

1.

3. The surface finishing method of the copper alloy inner flow channel structure manufactured by additive manufacturing according to claim 2 is characterized in that: The concentration of acetic acid in the acetic acid aqueous solution is 2-6 g / 100 ml; the concentration of the hydrogen peroxide aqueous solution is 10%-20%.

4. The surface finishing method of the copper alloy inner flow channel structure manufactured by additive manufacturing according to claim 1, characterized in that: The ambient temperature during the ultrasonic vibration is 30-40°C.

5. The surface finishing method of the copper alloy inner flow channel structure manufactured by additive manufacturing according to claim 4 is characterized in that: Under the temperature environment of 30-40℃, the hydrogen ions in the acetic acid aqueous solution react chemically with copper in the strong oxidizing environment of hydrogen peroxide, thereby dissolving and corroding the protruding parts of the inner surface of the copper alloy structure.

6. The surface finishing method of the copper alloy inner flow channel structure manufactured by additive manufacturing according to claim 4 is characterized by: Ultrasonic vibration is applied to the outer surface of the copper alloy structure, and vibration-chemical composite polishing is performed on the inner surface of the copper alloy structure.

7. The surface finishing method of the additively manufactured copper alloy inner flow channel structure according to claim 6, characterized in that: The frequency of ultrasonic vibration is 40-60kHz.

8. The surface finishing method of the copper alloy inner flow channel structure manufactured by additive manufacturing according to claim 6, characterized in that: Ultrasonic vibration causes the chemical polishing liquid to produce a cavitation effect on the surface of the copper alloy structure; the collapse of the cavitation produces an explosive jet that further improves the finishing efficiency and shortens the entire polishing time; the polishing time is 20-30 minutes.

9. The surface finishing method of the copper alloy inner flow channel structure manufactured by additive manufacturing according to claim 1, characterized in that: Clean the inner cavity 3-5 times with clean water.

10. The surface finishing method of the copper alloy inner flow channel structure manufactured by additive manufacturing according to claim 1, characterized in that: The temperature of the compressed air is above the dew point temperature; the pressure of the compressed air is 0.5-0.8Mpa.

Citation Information

Cited By

  • Method for improving quality of inner surface of inner runner part

    CN120866813A

  • Finishing method for additive manufacturing of fine complex inner flow channel

    CN121061755A